Stabilizing the commensurate charge-density wave in 1T-tantalum disulfide at higher temperatures via potassium intercalation. Issue 13 (14th March 2019) - Zhao, Rui; Grisafe, Benjamin; Ghosh, Ram Krishna; Wang, Ke; Datta, Suman; Robinson, Joshua
Abstract : The 1T phase of tantalum disulfide (1T-TaS2 ) possesses a variety of charge-density-wave (CDW) orders, and as a result, it attracts an increasing amount of academic and technological interest. Abstract : The 1T phase of tantalum disulfide (1T-TaS2 ) possesses a variety of charge-density-wave (CDW) orders, and as a result, it attracts an increasing amount of academic and technological interest. Researchers have devoted tremendous efforts towards understanding the impacts of doping, alloying, intercalation or other triggering agents on its charge density wave orders. In this work, we demonstrate that incorporating potassium chloride (KCl) during chemical vapor deposition (CVD) of TaS2 can control the phase (1T, 2H or metal nanowires) via the intercalation of potassium ions (K + ) between TaS2 layers. Finally, we demonstrate that K + not only impacts the structure during synthesis but also strongly impacts the CDW phase transition as a function of temperature, increasing the nearly commensurate (NCCDW) to commensurate (CCDW) transition to just below room temperature.